The cuckoo in the clock : ... and other stories - Blyton, Enid (London: Bounty Books, 2015)
A selection of short stories by Enid Blyton including The Cuckoo in the clock, Tubby Makes A Mistake, The Strange Sailor Doll, He'd Better Be Careful and The Doll in the Cushion.
Keywords: English , Fiction